Inovasi Pembelajaran dan Dampak Pandemi Di TK Assalam - Ela Latifah Fuadah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
This research is based on the problem of the Covid-19 pandemic which continues to increase every day so that changes occur in every sector including the education sector. With this change, innovation is needed so that learning can still be done even though it has to be at home. This research was conducted in Assalam Kindergarten, Tasikmalaya Regency. The research method used is descriptive qualitative method. Data collection and research used observation and interviews with 3 teachers and 3 parents at Assalam Kindergarten. Based on the results of observations in TK Assalam, it shows that there are 3 innovations carried out in TK Assalam, namely, 1) Learning at Home; 2) Home Visit or visiting students' homes; and 3) PTMT or limited face-to-face meetings. The impact of the COVID-19 pandemic is felt by all groups in PAUD institutions starting from educators, students to parents. The results of the research in the field show that learning innovations carried out such as learning from home, home visits and PTMT are indeed less effective because in their learning educators cannot see directly the potential of children when doing assignments, but hope that children are able to accept what the educators teach so that they can develop the potential of each child